Menyiasati Keterbatasan RKAP: Strategi Re-Alokasi Anggaran Program Baru Di PT. Y - Wafa Aisya Yusria Farjana; Nurul Fitriani (Universitas 17 Agustus 1945 Jakarta, 2026)
This study analyzes the budget re-allocation strategy used to fund new programs at PT. Y through re-prioritization and optimization of the current-year budget. PT. Y faces funding limitations for new programs because the Annual Work and Budget Plan (RKAP) value was fixed in the previous year, making internal re-allocation the only available solution. This research applies a descriptive qualitative case-study method, using in-depth interviews and internal documentation of PT. Y. Findings show that the main selection criteria are new-program items, large-value items, and low-realization items, identified through demand-driven and supply-driven approaches. The post-reallocation evaluation is effective because every shift is approved only after direct field inspection by leadership. The main challenge is the absence of available balances when urgent work arises. The study recommends formalizing re-allocation procedures and providing a contingency budget in future RKAP preparation.